OPTIMASI KOEFISIEN PARAMETER HIDROGRAF SATUAN SINTETIK ITB-1 DAN ITB-2 DI SUB DAS BIONGA KAYUBULAN - Endrizal Rahman Iyan; Barry Yusuf Labdul; Rawiyah Husnan (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Negeri Gorontalo, 2022)
The reduction of the unit hydrograph from the observed flood hydrograph is an important factor in water construction planning. However, it is difficult to obtain observational flood hydrograph data in the form of AWRL (Automatic Water Level Recorder) and ARR (Automatic Rainfall Recorder) data. Hence, the hydrograph reduction known as synthetic unit hydrograph (SUH) is developed. One of the synthetic hydrographs developed in Indonesia is SUHof ITB-1 and ITB-2. Based on this rationale, this study aimed to analyze the SUH of ITB-1 and ITB-2 in the Bionga Kayubulan sub-watershed. The Straight Line Method was employed to separate the base flow from the run-off in order to obtain a direct run-off hydrograph. In analyzing the effective rain, the study utilized the Φ index equation. Further, the direct run-off and effective rain hydrograph were reduced to the observation unit hydrograph using the Collins method. Additionally, Microsoft Excel-Solver software was used to optimize the SUH of ITB-1 and ITB-2 coefficients on the hydrograph of the observation unit. The hydrograph of the observation unit in the Bionga Kayubulan sub-watershed attained 4.5 hours peak time (Tp) with 2.81 /s peak discharge (Qp). The ITB-1 synthetic hydrograph in the site area attained 5.97 hours peak time (Tp) with 1.96 /s peak discharge (Qp), while the ITB-2 synthetic hydrograph attained 5.97 hours peak time (Tp) with 2.45 /s peak discharge (Qp). The calibration results of ITB-1 synthetic unit hydrograph with changed coefficient parameters showed the time coefficient (Ct) of 0.73, the peak coefficient (Cp) of 1.07, and alpha (α) of 1.60. Further, for the SUH of ITB-2, the results showed a time coefficient (Ct) of 0.73, a peak coefficient (Cp) of 0.96, alpha (α) of 2.50, and beta (β) of 0.95.